STRATEGI DINAS TENAGA KERJA DAN TRANSMIGRASI KOTA DUMAI DALAM MENGURANGI TINGKAT PENGANGGURAN DI KOTA DUMAI - Riska Dewi; Harapan Tua RFS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Unemployment is one of the main problems that is closely related to economic growth. But if the growth each year is only able to absorb less manpower than the number of job seekers, it will cause the number of unemployed to increase. Therefore, one thing that can be done to reduce the unemployment rate is to prioritize the interests of the citizens of Dumai City. As for the Dumai City Regional Regulation Number 4 of 2002 concerning the placement of local workers, it is appropriate for the government through related agencies to oversee recruitment. The purpose of this study was to find out how the strategy of the Dumai City manpower and transmigration office in reducing the unemployment rate in Dumai City and knowing the factors -what are the supporting factors in reducing the problem of unemployment rate. In this study, the theoretical concept used is the strategic theory put forward ( Ellitan & Anatan, 2008: 9), to measure the strategy set in an organization or company: technology strategy, innovation strategy and operations strategy. This research uses purposive sampling technique with qualitative research using the approach, phenomenalogy and data required both primary and secondary data obtained through observation, interviews and documentation then analyzed based on research problems. The results of this study indicate that: The strategy of the transmigration office of Dumai City in reducing the unemployment rate in the City of Dumai has not been running optimally. Supporting inhibiting factors include human resources and budget.Keywords: Technology Strategy, Innovation Strategy, Operations Strategy                       and  unemployment